Thermal performance estimation and optimisation of a shallow geothermal compound heat pumping system for combined process heating and cooling - J.E. De León-Ruiz; R. Beltrán-Chacón; I. Carvajal-Mariscal; M. Venegas; A. Ponsich (Results in Engineering)
The present study proposes a unique thermal loop assembly, between a ground-source vapour compression cycle and an absorption heat pump, for combined heating and cooling production. The feasibility of the setup is conducted through a, data-driven, thermal modelling approach. This is complemented by an optimisation implementation, as well as an economic assessment, based on a detailed case study. Performance was estimated using R134a, as well as 5 alternative refrigerants. The results show, that for all analysed cases, the proposed assembly meets required thermal needs, with adequate efficiency levels, i.e., COP > 3. Contrarily, changing working fluids does not exert a significant effect on the absorption loop performance. From the introduced operational stress indicators, it was found that, albeit yielding the highest COP, R1233zd(E) requires the highest displacement capacity of the analysed lot, making it unsuitable for this application. From the optimisation, it was found that R1234yf, is most suitable working fluid, with the smallest footprint whilst keeping manageable capacity requirements. Finally, the complementary economic assessment showed that this setup, on average, resulted in a 10.5 % gross energy cost reduction, based on doubling the batch processing rate. Based on this information, the presented compound system, is capable of boosting available source capacity, whilst simultaneously producing serviceable heating, cooling and residual outputs. Therefore, it is proposed as a viable alternative for heat pump loop assembly, as well as an alternative for applications beyond the case study here discussed.